P121 ECHOCARDIOGRAPHIC EXAMINATION ON AGONIST ATHLETES WITH RECENT PAUCISYMPTOMATIC SARS COV 2 INFECTION, FOR THE RENEWAL OF AGONIST SPORT ACTIVITY ELIGIBILITY: PLAUSIBLE ROLE AND UTILITY OF GLS ANALYSIS THROUGH SPECKLE TRACKING. (18th May 2022) - De Masi De Luca, G; Papadia, P; Prete, G; Nuccio, F; De Masi De Luca, G; Morciano, P; De Blasi, S
Abstract: Background: The aim of this work is to highlight whether or not the methodical echocardiography done through the analysis of global and segmental longitudinal deformation (GLS–SLS) can be useful to identify subclinical myocardial lesions in paucisymptomatic young agonist athletes with recent SarsCov2 infection before they return to agonist practice. Material and Methods: From 12/2020 to 12/2021 84 agonist athletes with previous SarsCov2 infection have been examined at "Cardiomed Center" Maglie (Lecce, IT), as part of screening for their return to sport practice; all of them under standard echocardiographic analysis associated to GLS analysis, Holter–ECG analysis with 24h on 12 derivations. Results: The base echocardiographic examination didn't show any myocardial cynesis anomalies in any patient. In 5 patients there was a presence of a light pericardial effusion, how it was supposed to be as an outcome of a previous inflammatory ingjury The GLS analysis, that resulted in reliability considering the optimal acoustic window, showed a slightly lower medium value compared to the values cited in the literature (19.4 ± 2.9) and particularly 4 patients show considerable deficit reductions of segmentary strain. In these patients Holter analysis showed the presence of a moderate non–complex extrasystolic arrhythmia. These elements–that are a reduced GLS with marked regional anomaly, coupled with the presence of ventricular arrhythmia even in absence of segmentary dissinergyes– led to cardiac RMN evaluation. In 2 out of 4 patients there have been flaws that were compatible to modest myocardial lesions, in one case it was observed a marked flaw in medium–apical–lateral region that was correlated to the described areas at the specle tracking. Conclusion: Our experience at the Cardiology and Sports integrated clinic, although it relied on a meager population of patients, it still demonstrated how echocardiographic analysis through GLS evaluation and the highlighting of sectorial alterations even in absence of cynesis anomalies can be used as a parameter to suppose the presence of miocarditic lesions that might be sent to the next RMN examination for confirmation, in young athletes with recent paucisymptomatic Covid–19 infection.